Covariant quantization of the superparticle using pure spinors - Berkovits, Nathan [UNESP] (Springer Nature, 2001)
The ten-dimensional superparticle is covariantly quantized by constructing a BRST operator from the fermionic Green-Schwarz constraints and a bosonic pure spinor variable. This same method was recently used for covariantly quantizing the superstring, and it is hoped that the simpler case of the superparticle will be useful for those who want to study this quantization method. It is interesting that quantization of the superparticle action closely resembles quantization of the worldline action for Chern-Simons theory.
Keywords: BRST symmetry; Superstrings and Heterotic Strings